On The Diophantine Equation:Jesmanowicz Conjecture And Selected Special Cases - Ahmed Balfaqih, Abdulrahman Hamed (2020)
In 1956, Jes´manowicz conjectured that for any primitive Pythagorean triple (a, b, c) with the Diophantine equation a2 + b2 = c2 and any positive integer k, the only solution of equation (ak)x +(bk)y = (ck)z, in positive integers, is (x, y, z) = (2, 2, 2). It is a famous unsolved conjecture on Pythagorean triples and exponential Diophantine equations, and generally it has not been solved yet. In this thesis, there are six chapters all together. The first chapter is on introduction of the thesis. Chapter 2 represents preliminaries and literature review.